Cooperative Output Regulation of Linear Multiagent Systems: An Event-Triggered Adaptive Distributed Observer Approach - Qian, Yang-Yang; Liu, Lu; Feng, Gang (IEEE transactions on automatic control, 2021)
This article investigates the cooperative output regulation problem for heterogeneous linear multiagent systems by event-triggered control, where the system matrix of the exosystem is not available to all agents. First, an event-triggered adaptive distributed observer is designed for each agent to estimate both the state and the system matrix of the exosystem. Then, a fully distributed event-triggered dynamic output feedback control law is proposed for each agent. Meanwhile, a fully distributed event-triggering mechanism is proposed such that each agent can determine when to broadcast its information to its neighbors. It is shown that with the proposed event-triggered control strategy, the cooperative output regulation problem is solved by intermittent communication in a fully distributed manner in the sense that no global information, such as the eigenvalues of the Laplacian matrix or the number of the agents, is used. It is also shown that Zeno behavior is excluded for each agent. Finally, a numerical example is given to illustrate the effectiveness of the proposed event-triggered control strategy.